2016
DOI: 10.1371/journal.pgen.1006458
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Lifespan in Yeast Is Dependent on the Accumulation of Storage Carbohydrates Mediated by Yak1, Mck1 and Rim15 Kinases

Abstract: Upon starvation for glucose or any other macronutrient, yeast cells exit from the mitotic cell cycle and acquire a set of characteristics that are specific to quiescent cells to ensure longevity. Little is known about the molecular determinants that orchestrate quiescence entry and lifespan extension. Using starvation-specific gene reporters, we screened a subset of the yeast deletion library representing the genes encoding ‘signaling’ proteins. Apart from the previously characterised Rim15, Mck1 and Yak1 kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 83 publications
7
76
0
Order By: Relevance
“…Puf5 promotes chronological lifespan (Stewart et al, 2007), which is dependent on the 294 accumulation of carbohydrates such as glycogen (Cao et al, 2016). Likewise, a ∆atp11 strain 295…”
Section: Overexpression Of Atp11 Rescues the Glycogen Accumulation Dementioning
confidence: 99%
“…Puf5 promotes chronological lifespan (Stewart et al, 2007), which is dependent on the 294 accumulation of carbohydrates such as glycogen (Cao et al, 2016). Likewise, a ∆atp11 strain 295…”
Section: Overexpression Of Atp11 Rescues the Glycogen Accumulation Dementioning
confidence: 99%
“…This adds yet another important physiological function to what has already been reported for its role in CWI signaling [4], the responses to high medium osmolarity (HOG pathway [6]) and oxidative stress, including the consequences for mitophagy and apoptosis [9,10], and the maintenance of chronological lifespan [24]. The notion that Rho5 fulfils the role of a central hub that integrates signals from different stress response and survival pathways [10] is further supported by the new findings presented herein.…”
Section: Discussionmentioning
confidence: 99%
“…However, regulation of the cell cycle shows poor correlation with the short‐lived phenotype of Rim15‐deficient cells; other TOR/Rim15‐dependent mechanisms such as carbohydrate storage seem to play a more important role (Cao et al., 2016). In agreement, we found that Ste12 regulation of cell cycle is not under the control of the TOR pathway, as rapamycin treatment did not affect G1 arrest in a ste12 ∆ background, suggesting that Ste12 controls cell cycle transitions in response to nutrients in a TOR‐independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is possible that Ste12 regulates lifespan through other mechanisms. Noteworthy, STE11 , an upstream component of the pheromone pathway, is also implicated in cell cycle and lifespan regulation (Cao et al., 2016). This supports the idea that Ste12 controls cell cycle transitions in response to nutrients and that the emergence of a G1‐arrested population is necessary for lifespan extension.…”
Section: Discussionmentioning
confidence: 99%